2011
DOI: 10.2165/11537080-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Flagellate Dermatitis as a Bleomycin-Specific Adverse Effect of Cytostatic Therapy

Abstract: In oncology, bleomycin is a frequently used drug for the treatment of several malignancies. In particular, it is part of chemotherapy protocols in testicular cancer. We report on two patients with testicular cancer who received bleomycin-including chemotherapy and developed flagellate dermatitis. This is a typical adverse effect of bleomycin therapy; however, its pathophysiology has not yet been clarified. We discuss possible pathophysiologic mechanisms for this reaction. In general, it has been postulated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 34 publications
1
80
0
3
Order By: Relevance
“…The linear or streaked pigmentation usually develops after a cumulative dose between 100-300 U of bleomycin (6,17), whereas considering our cases the cumulative doses were 38 U and 30 U. There are only 17 adult cases of FH following treatment with low-dose bleomycin (Table 1) (2,4,6,8,9,14,15,(17)(18)(19)(20)(21)(22)(25)(26)(27). It is observed that the majority of patients developing FH within 7 days of administration of bleomycin were young adults, even the dose of bleomycin was between 5-30 U.…”
Section: Discussionmentioning
confidence: 82%
“…The linear or streaked pigmentation usually develops after a cumulative dose between 100-300 U of bleomycin (6,17), whereas considering our cases the cumulative doses were 38 U and 30 U. There are only 17 adult cases of FH following treatment with low-dose bleomycin (Table 1) (2,4,6,8,9,14,15,(17)(18)(19)(20)(21)(22)(25)(26)(27). It is observed that the majority of patients developing FH within 7 days of administration of bleomycin were young adults, even the dose of bleomycin was between 5-30 U.…”
Section: Discussionmentioning
confidence: 82%
“…Flagellate dermatitis has also been reported in patients receiving other chemotherapeutic agents such as peplomycin, a bleomycin derivative, and docetaxel (12,13). Flagellate dermatitis can also occur in association with consumption of shiitake mushroom, dermatomyositis, adult-onset Still's disease and infection with human immunodeficiency virus (4,6). In most cases, the rash resolves spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the symptom of itch is the main treatment measure (14). Treatment with antihistamines and topical and oral corticosteroids may be required (4). Severe rash requires discontinuation of bleomycin (4).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Minor trauma to the skin, such as pressure over bony prominences and scratching, is thought to increase blood flow and cause local accumulation of bleomycin. 3 Flagellate dermatitis and subsequent hyperpigmentation in the skin is fairly common among patients receiving bleo mycin, with reported incidence between 8% and 22%. 3 Flagellate dermatitis is not typically associated with the other medications our patient was receiving.…”
mentioning
confidence: 99%
“…3 Flagellate dermatitis and subsequent hyperpigmentation in the skin is fairly common among patients receiving bleo mycin, with reported incidence between 8% and 22%. 3 Flagellate dermatitis is not typically associated with the other medications our patient was receiving.…”
mentioning
confidence: 99%